The effects of smoking and silica exposure on pulmonary epithelial permeability: a radioaerosol study with 99mTc-DTPA - Nery, L E; Sandoval, P R; Jardim, J R; Bagatin, E; Alonso, G (Brazilian journal of medical and biological research, 1988)
1. Pulmonary epithelial permeability (PEP) as evaluated by the clearance rate (K, %/min) of 99mTc-DTPA from lung to blood was measured in 4 groups of individuals: 10 normal controls; 10 smokers; 15 silica dust-exposed ceramic workers, 7 without chest X-ray alternations; and 8 with mild radiographic alterations, consistent with silicosis (small opacities of up to 1.5 mm diameter). 2. All subjects had normal pulmonary function tests. The mean clearance rates of smokers (3.0 %/min) and silica-exposed workers with X-ray changes (2.9 %/min) were accelerated compared to controls (1.2%/min) (P less than 0.05). Ceramic workers with normal X-rays had mean clearance rates (2.0 %/min) similar to controls. However, 3 of 7 (43%) had K values higher than the upper limit of the 95% confidence interval for the control mean. 3. Comparison of regional K (%/min) values with controls indicated faster clearance of 99mTc-DTPA in the upper lung regions of smokers. There was also increased clearance in the silicotic workers although of more uniform distribution over the lung regions analyzed. 4. Both smokers and ceramic workers exposed to a silica dust environment, with or without chest X-ray alterations, may show increased PEP compared to controls. As measurement of this parameter appears to be a sensitive index of lung injury, follow-up studies involving workers exposed to noxious dust are proposed to relate alterations in PEP to early silicosis and to the extent of lung injury.